Molecular Spectroscopy: A Quantum Chemistry Approach - Ozaki, Yukihiro; Wójcik, Marek Januz; Popp, Jürgen (John Wiley & Sons, Incorporated, 2019)
Uniquely creates a strong bridge between molecular spectroscopy and quantum chemistry This two-volume book consists of many reviews reporting new applications of quantum chemistry to molecular spectroscopy (Raman, infrared, near-infrared, terahertz, far-ultraviolet, etc.).